هندسة السلام: قراءة في المصطلح - لفحل ليندة (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
تتناول هذه الورقة اقتراح القيمة المتمثلة في استخدام نهج منتظم لتحقيق السلام الإيجابي وأهمية تطوير برامج مثل هندسة السلام لتزويد المهندسين بالمهارات والمعارف اللازمة بغية تمكينهم من العمل في أوضاع دولية معقدة وصعبة. فهناك حاجة وضرورة ملحة لتطوير مجموعة شاملة من المعرفة والممارسة في مجال هندسة السلام. كما يجب أن تأخذ مهنة هندسة السلام زمام المبادرة في إنشاء مجتمع صناعي للسلام قوي للغاية، وكما أنه قد يكون البديل للمجتمع الصناعي الحربي الحالي. This paper addresses the value proposition of using a systematic approach to positive peace and the importance of developing programs such as Peace Engineering to provide engineers with the necessary skills and knowledge to enable them to work in complex and challenging international situations. There is an urgent need and necessity to develop a comprehensive body of knowledge and practice in the field of peace engineering. The profession of peace engineering must also take the lead in creating a very powerful peace industrial society, as it may be an alternative to the present war industrial society.